Pre-operative preparation to anesthesia in children - Yu. S. Аleksandrovich; K. V. Pshenisnov (Вестник анестезиологии и реаниматологии)
The objective: the article is devoted to specific parameters of pre-operative preparation for anesthesia in children above 1 month old which is significantly different from adult practice. Special attention is paid to ensuring the psychological comfort of the child, collecting history and physical examination, which allows to assess the physical status of the patient, concomitant diseases and risk factors of airway obstruction during anesthesia. The article presents basic principles of anesthesia risk assessment in children and modern scales used for this purpose. It describes possible complications of anesthesia due to concurrent hereditary pathology in the child. Special parts of the article are devoted to pre-operative starvation, the problem of choice of premedication, specific pre-operative management in case of acute respiratory infections and acute surgical diseases of the abdomen.